A new desorption method of polyurethane foam for the determination of gold and a comparative study on four desorption methods based on meta-analysis. Issue 18 (20th April 2023) - Hou, Yaru; Lu, Jilong; Li, Mao; Wei, Qiaoqiao; Fan, Yuchao; Wang, Yongzhi
Abstract : Accurate gold determination in geological samples is important for studying geological problems. Here we perform a comparative study on four desorption methods based on meta-analysis and propose a new desorption method of polyurethane foam for gold determination. Abstract : Accurate determination of gold in geological samples is an important prerequisite and guarantee for studying geological problems. There are many methods for digestion and enrichment of gold among which polyurethane foam (PUF) enrichment after aqua regia digestion is the most commonly used in the experiments. A new method to help the relief of gold from the PUF was put forward in this study, and it was applied to four certified reference materials (CRMs) together with three previously used methods, and the optimal extraction and enrichment conditions were determined through experiments. The four methods were compared by meta-analysis, and the thiourea liberation method was superior to the other three methods because of its simple operation and high accuracy. Out of consideration for the incomplete adsorption of gold in the solution by only one piece of PUF, repetitive adsorption of gold with a second and a third piece of PUF in the solution was proposed in this study. Results show that the gold content obtained by secondary and tertiary adsorption accounts for 11.03% of the total content, and the highest can reach 20.74%. When the third adsorption was carried out, the gold content in several samples was below the detection limit. Therefore, repeated adsorption of gold in the solution is necessary, and three times of adsorption is necessary.